Mediation of Separation Anxiety in Psychological Distress and Insomnia in Parents Who Do Not Get Child Custody Due to Divorce - Marwa, Tsania; Satiadarma, Monty. P.; Roswiyani (Bisma The Journal of Counseling, 2024)
The divorce phenomenon often poses psychological problems for both the children and the parents. Most scientific studies are more focused on the impact of the divorces merely from the children’s side, not on the impact of divorce experienced by par-ents. Therefore, the objective of this study is to determine the relationship between psychological distress and insomnia disor-der mediated by separation anxiety in parents who do not get child custody due to divorce. There are 74 parents as partici-pants in this study who were divorced and losing custody with the age range of 20-40 years old. The measuring instruments used are The Depression Anxiety Stress Scale – 42 (The DASS-42) to measure psychological distress, insomnia severity index (ISI) to measure insomnia, and Adult Separation Anxiety – 27 (ASA-27) to measure separation anxiety. Using multiple linear regression analysis, this study found that separation anxiety plays a role in partially mediating the relationship between psy-chological distress and insomnia. This means that the higher the separation anxiety level, the higher the psychological distress and insomnia are experienced by the parents without custody. In addition, separation anxiety is proven more affecting the non-working parents compared to the working ones.